Redescription of two Hexactinosida (Porifera, Hexactinellida) from the southwestern Atlantic, collected by Programme REVIZEE - Lopes, Daniela A.; Hajdu, Eduardo; Reiswig, Henry M. (Zootaxa, 2005)
In this study, two species of hexactinosid sponges from the bathyal southwestern Atlantic (Hexactinosida, Hexactinellida), collected by Programme REVIZEE—Central Score, are redescribed and illustrated by scanning electron microscopy (SEM), viz., Aphrocallistes beatrix Gray, 1858 and Dactylocalyx pumiceus Stutchbury, 1841. This is the first redescription of A. beatrix based on extensive SEM use. Fourteen species of hexactinellid sponges are now recorded from the southwestern Atlantic, Aphrocallistes beatrix, Caulocalyx tener Schulze, 1886, Caulophacus abyssalis Tabachnick, 1990, Dactylocalyx pumiceus, Euplectella suberea Thomson, 1876, Holascus stellatus Schulze, 1887, Hyalonema schmidti Schulze, 1899, Hyalonema tenue Schulze, 1886, Malacosaccus heteropinularia Tabachnick, 1990, Pheronema carpenteri (Thomson, 1869), Rossella antarctica Carter, 1872, R. nuda Topsent, 1901, R. inermis (Topsent, 1916) and R. racovitzae Topsent, 1901.